Trehalose as an Endogenous Reserve in Spores of the Fungus Myrothecium verrucaria - Mandels, G. R. (1965)
Mandels, G. R. (U.S. Army Natick Laboratories, Natick, Mass.), Rasma Vitols, and Frederick W. Parrish. Trehalose as an endogenous reserve in spores of the fungus Myrothecium verrucaria. J. Bacteriol. 90:1589–1598. 1965.—Gross analysis of Myrothecium verrucaria spores showed approximately 3% fat, 33% carbohydrate, and 9.5% nitrogen. The water-soluble carbohydrates were trehalose, glucose, mannitol, and an unidentified phosphorylated compound. Water-soluble amino acids include leucine or norleucine (or both), valine, γ-amino-n-butyric acid, β-amino-n-butyric acid, ergothionine, glutamic acid, glutamine, glycine, aspartic acid, asparagine, cystine, and cystathionine. Ergosterol was also present. αα-Trehalose is the major reserve (20% of the dry weight), although approximately 30% of it appeared to be at the spore surface and was released by nonlethal treatment with 0.1 n HCl. Treatment with toluene or exposure to heat sufficient to kill the spores (20 min at 60 C) caused rapid liberation of all of the trehalose. Although spores could utilize exogenous trehalose with no appreciable lag, some stimulus, such as exposure to heat (10 min at 55 C), incubation with azide, or germination on exogenous substrates, was necessary to effect utilization of trehalose reserves. Spores have trehalase, but it is apparently at the spore surface, since it is inactivated by acid treatment which does not kill the spores. The metabolic pathway for utilization of trehalose is not known, but presumably it is not mediated by trehalase. The involvement of mannitol is indicated, since it tends to increase as trehalose decreases, although the changes are not quantitatively equivalent.